2012
DOI: 10.1111/j.1741-3729.2012.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication Technology and Postdivorce Coparenting

Abstract: Divorced individuals who share parenting responsibilities have to figure out ways to work together to raise their children. The purpose of this qualitative study of 49 divorced coparents was to examine how they used technology (e.g., cell phones, computers) to communicate. For parents in effective coparenting relationships, communication technologies made it easier for them to plan and make conjoint decisions about their children while living apart. Communication technology, however, did not necessarily make c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 29 publications
2
47
1
6
Order By: Relevance
“…Participants with informal custody arrangements use a particular method because it is comfortable for them, it is convenient, and it is their former partner's preferred method of communicating. Similar to the findings of Ganong et al (2012), coparents with formal custody arrangements use communication technologies to get things in writing and to avoid talking to the ex. Additionally for many informal custody arrangement coparents in this study, the method of communication differs depending on the topic or the urgency with which the participant needs to reach the former partner.…”
Section: Discussionsupporting
confidence: 72%
“…Participants with informal custody arrangements use a particular method because it is comfortable for them, it is convenient, and it is their former partner's preferred method of communicating. Similar to the findings of Ganong et al (2012), coparents with formal custody arrangements use communication technologies to get things in writing and to avoid talking to the ex. Additionally for many informal custody arrangement coparents in this study, the method of communication differs depending on the topic or the urgency with which the participant needs to reach the former partner.…”
Section: Discussionsupporting
confidence: 72%
“…However, the results are inconsistent. Mostly, researches focus on different ICTs (e.g., cell phone, videoconference) emphasizing partial variables of family functioning (e.g., cohesion, conflict) and are limited to specific stages of the family life cycle, such as couples (e.g., Bartholomew et al, 2012;Ganong et al, 2012;Schneider et al, 2012), families with children in school (e.g., Chesley & Fox, 2012;Lee & Chae, 2007) and families with adolescent children (e.g., Bacigalupe & Camara, 2011;Devitt & Roker, 2009;Mesch, 2003). In addition, besides to the five domains identified in this review another dimension transversal to these domains can be underlined: the stage of the family life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Freier and Kahn's (2009) collection of papers addressed how technological environments can be designed to foster rather than harm children's development. More recently, writers have shown that children can maintain relationships with friends and family members located in different cities or overseas (Longhurst 2013;Sime and Fox 2014), explore virtual landscapes with children from different backgrounds around the world (Ash and Gallacher 2011;Dezuanni, O'Mara, and Beavis 2015;Marsh 2010), or positively change learning and communication experiences for children with disabilities or absent and present caregivers (Ganong et al 2012;Holloway and Valentine 2003;Kagohara et al 2013). Freeman and colleagues in their paper (this collection) draw on notions of digital literacy to gain insights into children's use of nature in their neighbourhood via a child-operated Geographical Information System (GIS).…”
Section: Making Sense Of Children's Digital Worldsmentioning
confidence: 99%